Analisis Program Gerakan Literasi Sekolah di Sekolah dasar - Nur Ali Ardiansyah; Asep Usamah (Jurnal Riset Pendidikan Dasar (JRPD), 2024)
This research was motivated by the author's curiosity about how the school literacy movement program was implemented at SDN Kertaungaran, Sindangagung District, Kuningan Regency, with the aim of finding out how the school had implemented it and what were the supporting and inhibiting factors for the literacy movement in schools. This research uses descriptive qualitative methods using data collection techniques in the form of observation, interviews and documentation. The results of this research show that the implementation of the school literacy movement at SDN Kertaungaran has been running. The obstacles faced are students' lack of interest in reading, there are still students who cannot read and the lack of parental role in implementing literacy outside of school. Efforts that have been implemented by teachers include the existence of a reading corner, special guidance for students who are not used to reading, and giving rewards to students who read diligently.